Regulation of Mitochondrial Quality Control by Natural Drugs in the Treatment of Cardiovascular Diseases: Potential and Advantages - Chang, Xing; Zhang, Wenjin; Zhao, Zhenyu; Ma, Chunxia; Zhang, Tian; Meng, Qingyan; Yan, Peizheng; Zhang, Lei; Zhao, Yuping (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are double-membrane cellular organelles that can provide the required energy and metabolic intermediates to cardiomyocytes. Mitochondrial respiratory chain defects, structure abnormalities, and DNA mutations, as well as other mitochondria-related factors, can affect the normal function of cardiomyocytes, causing an imbalance in intracellular calcium ion homeostasis, production of reactive oxygen species, apoptosis, and other cellular and subcellular events. Mitochondrial quality control (MQC) is an important process that maintains mitochondrial homeostasis in cardiomyocytes and represents multi-level regulatory mechanisms, such as mitophagy, mitochondrial fission and fusion, mitochondrial energy metabolism, the mitochondrial antioxidant system, and the mitochondrial respiratory chain. Furthermore, MQC can participate in the pathological mechanism of various cardiovascular diseases (CVDs). In recent years, the regulatory effects of natural plants, drugs, and active ingredients on MQC in the context of CVDs have received extensive attention. Effective active ingredients in natural drugs can influence the production of energy-supplying substances in the mitochondria, interfere with the expression of genes related to mitochondrial energy requirements, and regulate various mechanisms of MQC modulation. Thus, the use of these ingredients in the clinical treatment of CVDs shows strong potential and advantages. This review provides information useful for the future treatment of CVDs and development of new drugs targeting MQC.